2021
DOI: 10.1021/acs.energyfuels.1c02955
|View full text |Cite
|
Sign up to set email alerts
|

Novel D–A−π–A Organic Dyes with Phenoxazine as a Donor Unit for Dye-Sensitized Solar Cells: The Effect of an Ethynyl Group on Performance

Abstract: We designed and synthesized two novel D–A−π–A organic dyes, POZ-4 and POZ-6, with phenoxazine (POZ) as the donor unit for application in dye-sensitized solar cells (DSSC). Our studies reveal that the introduction of the ethynyl group can optimize the planarity of the molecule and reduce the dihedral angle from 32° (POZ-4) to 2° (POZ-6), which promotes the intramolecular charge transfer (ICT) process. Hence, POZ-6 has a higher q CT value and more effective hole charge separation efficiency, ensuring that electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Nowadays, organic molecules having electron donor and acceptor groups in bridge framework (D-A) structures are extensively studied providing high molar extinction coefficients, stabilities, and higher electron injection efficiencies as well as due to their easy synthesis and tunable optical properties. 10,11 Besides the general use of such organic molecules, a distinctive charge transfer character is found in predominant use as a chromophore in advanced light-harvesting materials. However, unwanted exciton recombinations and narrow absorption windows are some of the major issues that have to be dealt with.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, organic molecules having electron donor and acceptor groups in bridge framework (D-A) structures are extensively studied providing high molar extinction coefficients, stabilities, and higher electron injection efficiencies as well as due to their easy synthesis and tunable optical properties. 10,11 Besides the general use of such organic molecules, a distinctive charge transfer character is found in predominant use as a chromophore in advanced light-harvesting materials. However, unwanted exciton recombinations and narrow absorption windows are some of the major issues that have to be dealt with.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the sensitizer’s constructional arrangement has been found to control pivotal exciton transfer phenomenon at the TiO 2 /sensitizer/electrolyte interfaces. Nowadays, organic molecules having electron donor and acceptor groups in bridge framework (D-A) structures are extensively studied providing high molar extinction coefficients, stabilities, and higher electron injection efficiencies as well as due to their easy synthesis and tunable optical properties. , Besides the general use of such organic molecules, a distinctive charge transfer character is found in predominant use as a chromophore in advanced light-harvesting materials.…”
Section: Introductionmentioning
confidence: 99%
“…A general framework based on a donor–acceptor system with π-spacers (D−π–A) induces intermolecular charge transfer (ICT) and determines the physicochemical properties of the device’s absorbing layer. Therefore, designing an appropriate structure is significant for developing efficient and stable DSSCs. Heteroaromatic units such as triphenylamine, carbazole, phenoxazine, phenothiazine, and imidazole are successfully used as electron-donating groups in D−π–A compounds. Especially interesting as donor blocks for dyes is the nonplanar phenothiazine conformation, which may inhibit molecular aggregation, lowering PV performance in DSSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Dihedral angles between the donor and acceptor units are seen to play an important role in efficient charge injection process by facile electronic communication. The D−A, D−π−A dyes with high planarity, and low dihedral angles between the donor and acceptor units, show better DSSCs performance due to dense packing of dyes on the TiO 2 [60,61] . It has been found that the dihedral angles between the aniline donor and acceptor moieties of D−A−D based squaraine dye AK2 (34.5°) compared to AK1 dye (0.05°) play an important role in modulating the photophysical as well as DSSCs performance [43] .…”
Section: Resultsmentioning
confidence: 99%
“…The DÀ A, DÀ πÀ A dyes with high planarity, and low dihedral angles between the donor and acceptor units, show better DSSCs performance due to dense packing of dyes on the TiO 2 . [60,61] It has been found that the dihedral angles between the aniline donor and acceptor moieties of DÀ AÀ D based squaraine dye AK2 (34.5°) compared to AK1 dye (0.05°) play an important role in modulating the photophysical as well as DSSCs performance. [43] The calculated dihedral angle values for AM dyes from the simulated geometry between the squaraine and aniline donor units was À 36.63°, À 41.26°and 37.98°for the AM1, AM2 and AM3 dyes, respectively (Figure 6).…”
Section: Computational Studiesmentioning
confidence: 99%